2004
DOI: 10.1002/tie.20023
|View full text |Cite
|
Sign up to set email alerts
|

Problems and challenges facing the islamic banking system in the west: The case of the UK

Abstract: Executive SummaryThis study investigates the main problems, challenges, and opportunities facing Islamic banking in the United Kingdom. The study reports the results of interviews that were undertaken with senior officials of several key financial institutions who have had many years of experience in dealing with Islamic banking. Our interviews revealed that, although by strict definition Islamic banks do not currently exist in the UK, London is one of the major centers for Islamic banking and finance. It is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 4 publications
1
51
0
Order By: Relevance
“…The interviews also revealed that the main problem that Islamic banking faces in the UK is heterogeneous clients and potential clients. Moreover, regulatory hurdles, competition from conventional banks, and lack of adequately qualified and trained personnel exacerbate the situation (Karbhari, Naser & Shahin, 2004). Fatwa is basically a religious ruling on matter of Islamic laws not clearly mentioned in Shariah.…”
Section: Notwithstanding Ofmentioning
confidence: 99%
“…The interviews also revealed that the main problem that Islamic banking faces in the UK is heterogeneous clients and potential clients. Moreover, regulatory hurdles, competition from conventional banks, and lack of adequately qualified and trained personnel exacerbate the situation (Karbhari, Naser & Shahin, 2004). Fatwa is basically a religious ruling on matter of Islamic laws not clearly mentioned in Shariah.…”
Section: Notwithstanding Ofmentioning
confidence: 99%
“…The first generation of Islamic banks was developed in Egypt and Malaysia in the 1960s, although the Egyptian experiment did not last very long, and it was not until the mid 1970s when it started to take hold in many Muslim countries (Karbhari et al, 2004). The 1970s saw two oil-price shocks, which led to a massive transfer of wealth from the oil-consuming to the oil-producing countries.…”
Section: History and Growth Of Islamic Banking And Financial Institutmentioning
confidence: 99%
“…IBF are fundamentally different from conventional banking because IBF institutions principally operate on the basis of Sharia law, which prohibits the charging of interest (Hassan, Kayed, & Oseni, 2013;Hassan & Lewis, 2014). According to Karbhari, Naser and Shahin (2004), Islamic banks may function in countries adopting Islamic Sharia principles (e.g., Malaysia, Iran, Pakistan, and Sudan), or function in predominantly Muslim countries along with conventional banks (Arab and Muslim countries), or function in predominantly non-Muslim countries along with conventional banks (Western countries).…”
Section: Introductionmentioning
confidence: 99%